(untitled) (The Pakistan Development Review, 1986)
This paper develops and estimates a monetary model of inflation in Pakistan over the 1963 -82 period. Both domestic and external factors are identified as the major determinants of inflation. Dynamic simulation results suggest that the model is able to track the fluctuations of endogenous variables and, most importantly, the inflation explosion during the 1970s is clearly predicted by the inflation equation.